2013
DOI: 10.1603/en12325
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Spread of an Invasive Termite in an Urban Environment Using a Stochastic Individual-Based Model

Abstract: Invasive termites are destructive insect pests that cause billions of dollars in property damage every year. Termite species can be transported overseas by maritime vessels. However, only if the climatic conditions are suitable will the introduced species flourish. Models predicting the areas of infestation following initial introduction of an invasive species could help regulatory agencies develop successful early detection, quarantine, or eradication efforts. At present, no model has been developed to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…However, some of these models have neglected the effects of life history traits (Grevstad 2005;Huang et al 2008), landscape heterogeneity and changes Grevstad 2005;Buhle et al 2012;Geetal.2013)and tideland elevation Buhle et al 2012). Spatially explicit individual-based models account for not only the life history of the target species, but also its dispersal progress and abiotic factors such as landscape heterogeneity and changes, which are widely used in population dynamics simulations (Lo´pez-Alfaro et al 2012;Tonini et al 2013;Cohen et al 2014). Remote sensing (RS) and Geography Information System (GIS) are important tools that reveal the changing vegetation patterns associated with broad-scale plant invasions (Civille et al 2005;Z h a n ge ta l .2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these models have neglected the effects of life history traits (Grevstad 2005;Huang et al 2008), landscape heterogeneity and changes Grevstad 2005;Buhle et al 2012;Geetal.2013)and tideland elevation Buhle et al 2012). Spatially explicit individual-based models account for not only the life history of the target species, but also its dispersal progress and abiotic factors such as landscape heterogeneity and changes, which are widely used in population dynamics simulations (Lo´pez-Alfaro et al 2012;Tonini et al 2013;Cohen et al 2014). Remote sensing (RS) and Geography Information System (GIS) are important tools that reveal the changing vegetation patterns associated with broad-scale plant invasions (Civille et al 2005;Z h a n ge ta l .2011).…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of termite colony spread developed by Tonini et al (2013) shows a rapid increase in the area affected during the first two years of the invasion, followed by continued growth in the size of this area, but at a much slower rate (Figure 1). In 2015, after a full year of allowing the termite invasion to run its course, the simulation shows colonies expanding, but only in the cells that are immediately adjacent to the initial termite colonies.…”
Section: Colony Spread Simulationmentioning
confidence: 99%
“…The individual-based model by Tonini et al (2013) was used to simulate the spread of C. gestroi over Grand Cayman from 2014 to 2050. The values used in the model for the main ecological parameters (Tonini et al 2013) are shown in Table 1.…”
Section: Spread Model For C Gestroi On Grand Caymanmentioning
confidence: 99%
“…The individual-based model by Tonini et al (2013) was used to simulate the spread of C. gestroi over Grand Cayman from 2014 to 2050. The values used in the model for the main ecological parameters (Tonini et al 2013) are shown in Table 1. Because of the stochastic nature of the model used, 100 replications were run to account for the uncertainty associated with the outcome of a stochastic simulation.…”
Section: Spread Model For C Gestroi On Grand Caymanmentioning
confidence: 99%
See 1 more Smart Citation